Highly reversible and stable manganese(II/III)-centered polyoxometalates for neutral aqueous redox flow battery - Wenjin Li; Peng Luo; Zhiyong Fu; Xianzhi Yuan; Mingbao Huang; Kai Wan; Zhipeng Xiang; Zhenxing Liang (Next Energy, 2023)
Manganese (Mn) is a promising positive electrode element for aqueous redox flow batteries (ARFB); however, reversible and stable Mn species are still highly desirable. Herein, an ultra-stable Mn-centered Keggin-type polyoxometalate, viz. (NH4)6[MnW12O40]·9 H2O, is designed for neutral ARFB. The polyoxometalate is extensively characterized by X-ray crystalline diffraction, ultraviolet-visible spectroscopy, X-ray photoelectron spectroscopy, and electrochemical method. It is found that for (NH4)6[MnW12O40], the rigid skeleton and cage-structural coordination yield superior stability in a symmetrical flow battery. Pairing with viologen derivative, 0.50 M (NH4)6[MnW12O40] flow battery delivers a capacity of 10.2 Ah L−1 and a capacity retention ratio of 99.994% per cycle at 20 mA cm−2 over 500 cycles (∼19 days). This work provides new insight into designing stable electroactive materials for ARFB.